Impact of Organizational Factors on Job Stress in IT Companies - Mohana, Dr. S.; Deepti, Dr. V.; Santosh, Mr. Kathari (The journal of contemporary issues in business and government, 2023)
This research article aims to “To study the impact of different organizational factors on job stress of IT professionals”. The paper applies data reduction using Exploratory Factor Analysis (EFA) on a sample of 312 respondents drawn from 6 IT companies in the Bengaluru and condenses a set of 16 organizational factors converted into a four organizational factors. The present study proposes a model of the impact of organizational factors on job stress. The study found that organizational snags, sedentary self, adaptability to situations and hierarchical pressure are impacting significantly the job stress. Therefore, IT companies should focus on the above factors to reduce job stress of professionals. The study investigated the impact of organizational factors on job stress of the IT professionals concluded that organizational snags had the highest impact on the job stress of the professionals’ sedentary self, adaptability to situations followed by hierarchical pressure.